Emission of Greenhouse Gases and Ammonia from the Excreta of Nellore Bulls Submitted to Energy and Tannin Supplementation - Rigobello, Izabela Larosa [UNESP]; Cardoso, Abmael da Silva; Fonseca, Natalia Vilas Boas [UNESP]; Ongaratto, Fernando; Silva, Matheus Mello [UNESP]; Bahia, Angelica Santos Rabelo de Souza [UNESP]; Dornellas, Isadora Alves [UNESP]; Reis, Ricardo Andrade [UNESP] (MDPI, 2023)
Animal supplementation during the background phase may increase greenhouse gas emissions (GHG). The inclusion of tannins in the diet of Nellore bulls can mitigate nitrous oxide (N2O), methane (CH4), and ammonia (NH3) production. The objective of this study was to quantify the effect of energy supplementation associated with sources of tannins in the diet of young Nellore bulls backgrounded in pastures with N2O, CH4, and NH3 emissions. Two experiments were conducted in a completely randomized design. The treatments were three supplementation strategies: (1) soybean hulls 0.3% of body weight (BW), (2) sorghum grain 0.3% of the BW, and (3) peanut peel 0.3% of BW, the last two being sources of tannin. The static closed chambers method was used to quantify N2O and CH4 emissions and the semi-open chamber technique to estimate NH3 volatilization. Supplementation strategies did not affect the N2O emissions (p = 0.9116). The soil water-filled pore space explained the variation in the N2O fluxes (p = 0.0071). The treatments did not change the total CH4 emissions (p = 0.3599), and no explanatory variable was correlated with the CH4 fluxes. The NH3 volatilization did not vary according to the supplements or tannin inclusion (p = 0.5170). However, the type of excreta affected the NH3 volatilization (p < 0.0001). Ammonia volatilization averaged 14.05, 4.16, and 2.25% of the applied N for urine, urine + dung, and dung, respectively. The energetic supplementation of Nellore bulls containing sources of tannins in the evaluated dosages was not a mitigation strategy for the emissions of N2O, CH4, and NH3.
Keywords: greenhouse gases; livestock; mitigation; Nellore bulls; supplementation